An Analysis of the Training Path of Computer Thinking Ability in Higher Vocational Computer Teaching - Gao, Tianfang (Journal of Education and Educational Technologies, 2023)
Higher vocational computer is a basic discipline and one of the important courses in higher vocational colleges. It is very important to improve the computer professional level of higher vocational students. Mastering a solid computer foundation will help students apply the skills they have learned well into practice, and continue to expand their knowledge to make themselves more competitive. Computer knowledge learning requires good computer thinking and solving problems with computer thinking. This article mainly expounds the measures to cultivate students' thinking ability in computer in higher vocational education in China. To provide some meaningful reference opinions for the cultivation of computer thinking ability of students in higher vocational computer teaching in China.